The drought resilient farm - Strickler, Dale (North Adams, MA : Storey Publishing, 2018)
Defend and fortify your crops, soil, pasture, and livestock against inadequate rainfall -- and even chronic drought -- with strategies from a sixth-generation Kansas farmer and agronomist that will restore soil productivity through grazing, soil microbiology, and cover crops. Dale Strickler shares the lessons he's learned while saving his own family farm from drying up, including installing rain-collection tanks, creating swales, and building retention dams. With Strickler's friendly advice and proven, innovative methods, you'll get more water into your soil, keep it in your soil, and help your plants and livestock access it.--COVER.
Introduction: the ugly history of drought and the potential for drought resilience -- Getting more water into the soil -- Keeping water in the soil longer -- Helping plants get more water out of the soil -- Ensuring livestock water supply -- Creating drought-tolerant pastures -- Providing emergency forage in a drought -- Livestock decisions during and after the drought -- Moisture-efficient agriculture for the semi-arid regions -- Conclusion, and a checklist of actions to take before and during the next drought.
Includes bibliographical references and index.
107056
Keywords: Water conservation; Droughts; Soil moisture; Livestock -- Water requirements; Agriculture